2006
DOI: 10.2106/jbjs.e.01375
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Safe Area for the Axillary Nerve in the Deltoid Muscle?

Abstract: The present study describes a safe area above the axillary nerve that is quadrangular in shape, with the length of the lateral edges being dependent on the individual's arm length. Using this safe area should provide a safe exposure for the axillary nerve during shoulder operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
37
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 16 publications
3
37
1
4
Order By: Relevance
“…32 Straight posterior penetration of the central posterior humeral cortex in this anatomic area avoids injury to the axillary nerve and posterior circumflex humeral artery located more proximally at the level of the humeral neck and to the radial nerve and brachial profunda artery located more medially and posteriorly. [33][34][35][36] Previous techniques have been associated with postoperative immobilization of up to 6 weeks and return to full activities as late as 6 months after biceps tenodesis. 9,13,20,22,25 The described tenodesis technique using a combined endobutton and interference screw fixation allows for more rapid postoperative mobilization with active motion starting at 1 week after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…32 Straight posterior penetration of the central posterior humeral cortex in this anatomic area avoids injury to the axillary nerve and posterior circumflex humeral artery located more proximally at the level of the humeral neck and to the radial nerve and brachial profunda artery located more medially and posteriorly. [33][34][35][36] Previous techniques have been associated with postoperative immobilization of up to 6 weeks and return to full activities as late as 6 months after biceps tenodesis. 9,13,20,22,25 The described tenodesis technique using a combined endobutton and interference screw fixation allows for more rapid postoperative mobilization with active motion starting at 1 week after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…According to many authors, the safe zone for splitting the deltoid superior to the axillary nerve varies from 38 mm 6 to 40 mm 11 or 52 mm. 5 Cetik et al suggested using a ratio of arm length to predict the position of the axillary nerve, with a ratio of 0.20 anteriorly and 0.16 posteriorly. 5 Burkhead et al found that the axillary nerve in women was significantly closer to the acromion by 10 mm in his dissections.…”
Section: Discussionmentioning
confidence: 99%
“…5 Cetik et al suggested using a ratio of arm length to predict the position of the axillary nerve, with a ratio of 0.20 anteriorly and 0.16 posteriorly. 5 Burkhead et al found that the axillary nerve in women was significantly closer to the acromion by 10 mm in his dissections. 4 Given the established variable location of the nerve and that previous studies have already determined that gender and arm length affect the distance of the axillary nerve with respect to the acromion, this study did not attempt to quantify the exact position of the nerve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is commonly noted that the anterior trunk of the axillary nerve crosses the lateral humerus on the subfascial surface of the deltoid muscle 3-7 cm inferior to the lateral corner of the acromion. 27,[29][30][31][32][33] It is this branch that is at greatest risk during plate application and screw insertion and is the branch that was injured in the case presented. Based on an understanding of this anatomy, many authors previously recommended that surgical incisions about the shoulder be limited to within 3-5 cm of the lateral aspect of the acromion.…”
Section: Discussionmentioning
confidence: 99%